ACT untuk Meningkatkan PGI Mahasiswa Sarjana yang Mengalami Depresi, Kecemasan, atau Stres - Diptya Ratri Pratiwi; Imelda Ika Dian Oriza (Jurnal Ilmiah Psikologi MIND SET, 2022)
This study aims to examine the effectiveness of web-based Acceptance and Commitment Therapy (ACT) intervention in improving personal growth initiative (PGI) in undergraduate students who experience depression, anxiety, or stress. Levels of depression, anxiety, and stress were measured using the Depression Anxiety Stress Scales (DASS-42), while PGI was measured using the Personal Growth Initiative Scale II (PGIS-II). One-group pretest-posttest design with additional follow-up measurement were used in this study. Assessments were conducted before, after and two weeks after the intervention was implemented. The web-based ACT intervention was carried out for one month using Universitas Indonesia's Student Centered e-Learning Environment (SCeLE) system and consisted of eight sessions. Data processing using Friedman Test and Wilcoxon Signed-Rank Test showed that PGI significantly increased (p < 0.017) following the web-based ACT intervention. This study also showed that the level of depression, anxiety, and stress of undergraduate students significantly reduced (p < 0.017) following the web-based ACT intervention.